Magnetic properties of composite (1-x)BiFeO3-xBa5PrTi3V7O30 - Hage Doley (Dera Natung Government College Research Journal)
Ceramic composite of (1-x)BiFeO3-xBa5PrTi3V7O30 with different x values are prepared by using high-temperature solid-state reaction technique. Magnetic measurement is done at low temperature by PPMS Vibrating Sample Magnetometer which shows that the magnetization is maximum for x=0.3